Exploring the achievement levels of successful professional photographers in Chongqing, China - Yang, Yanlin; Alias, Jamsari Bin; Awang, Mohd Mahzan Bin; Rahim, Syafiqah Abdul (Edelweiss Applied Science and Technology, 2025)
This study investigates the multidimensional achievement levels of professional photographers in Chongqing, China, employing a qualitative methodology grounded in case studies and grounded theory. Through purposive sampling, three accomplished photographers specializing in photography education, astrophotography, and wedding photography were selected. Data collected via semi-structured interviews, video dialogues, and telephonic follow-ups were analyzed using NVivo software, adhering to the three-stage coding process of grounded theory. Results reveal that photographers’ achievements encompass five core dimensions: Industry status, professional competence, work value, influence, and professional ethos. Divergent priorities emerged: commercial photographers prioritized market competitiveness and client satisfaction, while art photographers emphasized cultural expression and creative autonomy. Regional dynamics, such as leveraging Chongqing’s "mountain city" cultural symbols and navigating technological disparities, critically shaped achievement trajectories. The study proposes a region-driven achievement model, integrating Bourdieu’s capital theory with localized cultural and technological ecosystems. It advocates for multidimensional evaluation frameworks balancing objective metrics and subjective values. Practical implications include curriculum reforms aligning photography education with regional industry demands and policy initiatives to foster cross-sector collaborations. This research enriches discourse on non-metropolitan creative industries, offering insights for talent development and sustainable cultural economies in transitional contexts.